A Themed Issue Dedicated to Professor John B. Goodenough on the Occasion of His 100th Birthday Anniversary (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book of Molecules is dedicated to Professor John B. Goodenough (born July 25, 1922, Jena, Germany), an American physicist, who won the 2019 Nobel Prize for Chemistry for his work on developing lithium-ion batteries.